Analysis and control of aquatic locomotion on robotic fish - Poddar, Rohit (2015)
Biomimetics has been a vibrant research field over the years with the rationale that natural systems have developed over millions of years of evolution and hence tend to provide better efficiencies. This project is focused on the design and control of a robotic shark. The major aim was to develop the robot’s body similar to a shark’s both in shape and locomotion. The short-fin MAKO shark was chosen for this project, as the MAKO is the fastest among all shark species. A major part of the project focused on the design of the robot’s body so as to most closely mimic an actual shark. Another facet of the research was to create a locomotion system that would resemble an actual shark’s undulating caudal fin. To achieve this, a cable-based system was used. The students eventually created a skeleton structure for the robot, which was then covered with low-density plastic. The control system was then designed on the Arduino microcontroller aimed at simplicity and faster response time. Experiments were then carried out on this model inside the testing tank. The concept of dynamic lift was used in the robot as it provided better response time than static-based systems. Moreover, the actual MAKO employs a similar mechanism through the use of its pectoral fins. Overall, this report details the design, assembly and control of the robotic shark. It also highlights the key experimental results pertaining to these aspects of the project. However, additional experiments and testing need to be carried out to further optimize the design of this robot and maximize its efficiency.